Hubungan Rasio Tenaga Kerja Dan Tenaga Pengawas Dengan Produktivitas Perusahaan Pengalengan Di Kota Bitung - Manueke, Yosua Azarya; Mandei, Juliana Ruth; Kapantow, Gene Henfried Meyer (Sam Ratulangi University, 2023)
This study aims to analyze the relationship between the ratio of the number of workers and supervisory staff with the productivity of fish canning companies. The research data was taken directly at 2 Fish Canning Companies in Bitung City, North Sulawesi Province, namely PT Sinar Pure Foods International and PT Deho Canning. The research was conducted for 3 months from May to July 2022. This research was conducted at 2 Fish Canning Companies in Bitung City, North Sulawesi Province, namely PT Sinar Pure Foods International and PT Deho Canning. The data used in this research is primary data. Data obtained from companies that have been arranged in the form of written documents from the company under study. The data used is monthly data in the last three years of the company, namely 2018 to 2020. The data was then analyzed using correlation analysis techniques. The results showed that the relationship between Labor and Supervisory Labor Ratio (X) and Productivity (Y), from the two companies studied, namely PT.Deho Company and PT.Sinar Pure Foods International in 2018 to 2020, showed a Pearson Correlation result of -0.136 and a Significance of 0.258. Although statistically this correlation is not significant, the direction of this correlation shows a tendency that the greater the ratio value, or the less supervisory personnel, the productivity will decrease.